Glyphosate Residues in Soil and Phosphate Fertilizer Affect Foliar Endophytic Microbial Community Composition and Phytohormone Levels in Potato - Suni Anie Mathew; Aditya Jeevannavar; Marjo Helander; Manu Tamminen; Pere Puigbò; Miia Rainio; Kari Saikkonen; Benjamin Fuchs (Phytobiomes Journal)
Glyphosate, the active ingredient of glyphosate-based herbicides (GBHs), controls the growth of weeds by inhibiting the shikimate pathway, thereby interrupting amino acid biosynthesis in plants. However, several microbes have the shikimate pathway, and the effect of glyphosate on these non-target organisms is ignored. The action of GBHs is further complicated when used with other agrochemicals, such as phosphate fertilizers, often varying their mode of action depending on soil type or plant species. To address the impact of GBHs and phosphate fertilizers, we simulated agricultural application of GBHs and phosphate fertilizers in a field study, investigating the composition of endophytic microbial communities and correlation of phytohormone concentrations with the microbial diversity of potato (Solanum tuberosum). In leaves, glyphosate residues in soil from GBH treatment alone and in combination with phosphate significantly shifted the bacterial community, whereas phosphate alone and in combination with glyphosate significantly altered the composition of the fungal community. There were no significant changes in microbial communities in roots and tubers. Plants treated with GBHs showed higher ratios of potentially glyphosate-resistant bacteria, with Xanthomonadaceae and Moraxellaceae being more abundant. Additionally, phytohormone concentrations showed various correlations with bacterial and fungal diversity in different treatments. The study highlights the impact of GBH residues in soil, particularly in combination with phosphate fertilizers, on the composition of plant-associated microbial communities. Together with changes in phytohormone concentrations, plant health may be affected. Future studies could provide insights into whether these agrochemicals influence the plant microbiome, leading to changes in phytohormones or vice versa. [Figure: see text] Copyright © 2024 The Author(s). This is an open access article distributed under the CC BY 4.0 International license.